CITIZEN JOURNALISM SEBAGAI MEDIA EMANSIPATIF DI GRUP FACEBOOK “INFO LANTAS MOJOKERTO” - Puji Laksono (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2021)
ABSTRACTDevelopment of the flow information which much accompained with the rapid to grow up of technology to made information an important part of human life. Today social media is an populer to use find, get, and provide information. With the rapid use of social media particularly facebook make information uncontrollable such as hoax, bullying, hate speech, and etc. the purpose in a research to find how citizen journalism as emancipative media in facebook group “Info Lantas Mojokerto”. Using the Phenomenom of citizen journalism that fills the public sphere of social media, especially facebook which makes colorfull a information flow. Public sphere provided by social media is able to facilitate people to exchange opinion and share information in a democration place and there is’t intervension from anywhere. Create a space that is free to expresion opinion but must comply with regulation in public sphere such a group facebook “info lantas mojokerto”. Theory used is a theory of the publick sphere put forward by Jurgen Habermas. This research was conducted on citizen journalism in the facebook group “Info Lantas Mojokerto”. The study use qualitative method to describe and explain finding in the field. Collection data using interview, observation, and documentation techniq. Analisis technique used in descriptive analysis.Result showed that citizen journalism in the facebook grup “Info Lantas Mojokerto” have a role an importan as social control to environment where each one lives. As well showing that the facebook group “Info Lantas Mojokerto” can play role that is easily accesible to the wider community, without any intervention from any parts, not part of govermen and owned of media or companies, and can be an equal or emancipatory place for all people without looking of their background.Key words: Citizen Jornalism, Public Sphere, Emansipative Media